Corneal Backscatter Analysis by In Vivo Confocal Microscopy: Fellow Eye Comparison of Small Incision Lenticule Extraction and Femtosecond Laser-Assisted LASIK - Alper Agca; Engin Bilge Ozgurhan; Yusuf Yildirim; Kadir Ilker Cankaya; Nimet Burcu Guleryuz; Zeynep Alkin; Abdullah Ozkaya; Ahmet Demirok; Omer Faruk Yilmaz (Journal of Ophthalmology)
Purpose. To evaluate and compare corneal backscatter from anterior stroma between small incision lenticule extraction (SMILE) and femtosecond laser-assisted LASIK (femto-LASIK). Methods. A cohort of 60 eyes of 30 patients was randomized to receive SMILE in one eye and femto-LASIK in the fellow eye. In vivo confocal microscopy was performed at 1 week and 1, 3, and 6 months after surgery. The main outcome measurements were maximum backscattered intensity and the depth from which it was measured, the backscattered light intensity 30 μm below Bowman’s membrane at the flap interface and 150 μm below the superficial epithelium, and the number of refractive particles at the flap interface. Results. The mean backscattered light intensity (LI) at all measured depths and the maximum backscattered LI were higher in the SMILE group than the femto-LASIK group at all postoperative visits. LI differences at 1 week and 1- and 3-month visits were statistically significant (P<0,05). LI differences at 6 months were not statistically significant. There was no difference in the number of refractive particles at the flap interface between the groups at any visit. Conclusions. SMILE results in increased backscattered LI in the anterior stroma when compared with femto-LASIK were evaluated.